HIF-1α inhibition promotes the efficacy of immune checkpoint blockade in the treatment of non-small cell lung cancer - Luo, Fan; Lu, Fei-Teng; Cao, Jia-Xin; Ma, Wen-Juan; Xia, Zeng-Fei; Zhan, Jian-Hua; Zeng, Kang-Mei; Huang, Yan; Zhao, Hong-Yun; Zhang, Li (Cancer letters, 2022)
The response to immune checkpoint inhibitors (ICIs) monotherapy remains unsatisfactory in patients with NSCLC. Thus, combining ICIs with other potential modalities is of great significance to enhance the response of single drug alone. Here, we identified that HIF-1α inhibition was capable of promoting anti-tumor immunity in NSCLC. We applied NSCLC cell lines and mouse models to evaluate the synergy of combined HIF-1α inhibition and PD-1 blockade on tumor growth and the function of tumor infiltrating lymphocytes (TILs). Public datasets were utilized to investigate patients' prognosis based on expressions of HIF-1α and LOXL2 as well as EMT-associated markers and CD8+ TILs. Moreover, we explored the correlation between HIF-1α and LOXL2 levels and CD8+ TILs in tumor samples from patients with NSCLC by immunohistochemistry, as well as their association to patients’ survival. In vitro, PX-478, an HIF-1α inhibitor, promoted tumor cell apoptosis induced by T cells when combined with ICIs. Furthermore, mice treated with PX-478 and anti-PD-1 antibodies exhibited a marked delay in tumor growth and prolonged survival, which correlated with increased TILs and granzyme B secretion. Besides, patients with high HIF-1α expression exhibited high levels of EMT-related markers and low TILs, indicating an immunosuppressive phenotype. Mechanistically, we observed that HIF-1α inhibition suppressed the EMT phenotypes induced by hypoxia and further alleviated tumor immunosuppression, which was related to blockage of HIF-1α/LOXL2 signaling pathway. In summary, we identified that HIF-1α inhibition could synergize with anti-PD-1 to impair tumor growth in vitro and in vivo. Our data suggest that HIF-1α inhibitors represent a promising treatment to enhance anti-tumor immunity and provide preclinical rationale to evaluate the combination of ICIs with HIF-1α inhibition clinically in NSCLC. •Attenuating hypoxia-induced EMT phenotypes may increase tumor infiltrated activating T cells.•Downregulation of EMT by HIF-1α inhibition was associated with suppression of the HIF-1α-LOXL2 signaling pathway.•The combination of HIF-1α inhibition and ICIs can induce significant tumor regression and improve efficacy of immunotherapy.